Non-violation and situation complaints under the TRIPS Agreement: Implications for developing countries - Nirmalya Syam (South Centre, 2020)
While the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS) provided for the applicability of non-violation and situation complaints to the settlement of disputes in the area of intellectual property (IP), when the World Trade Organization (WTO) agreements were adopted in 1994, a moratorium was put in place until WTO Members could agree on the scope and modalities for the application of such complaints. However, for more than two decades, discussions in the TRIPS Council on the subject have remained inconclusive. The biannual WTO Ministerial Conference has granted extensions of the moratorium with regularity. This paper reviews the debate on the applicability of non-violation and situation complaints under the TRIPS Agreement, including the arguments consistently held by two WTO Members that if the moratorium is not extended by consensus, non-violation and situation complaints would become automatically applicable. This paper argues that a consensus decision by the WTO Ministerial Conference is required to determine the scope and modalities and, hence, the applicability of such complaints under the TRIPS Agreement. Even if the moratorium was not extended, the WTO Ministerial Conference should still adopt a decision calling on the TRIPS Council to continue examination of the scope and modalities of such complaints. It also argues that in the absence of an extension of the moratorium on initiating such complaints—and although they would not be applicable—a situation of uncertainty would be created that may lead to a de facto limitation in the use of flexibilities allowed under the TRIPS Agreement.
Keywords: 300; Access to Medicines; Affordable Medicines; Appellate Body; Compulsory Licenses; Data Exclusivity; Dispute Settlement; Doha WTO Ministerial Decision on Implementation-Related Issues and Concerns; Evergreening; Flexibilities; GATS; GATT; Genetic Resources; Intellectual Property; Intellectual Property (IP) Enforcement; Least Developed Countries (LDCs); Ministerial Conference; Moratorium; Non-Violation Complaints; Patent; Patent Examination; Patent Linkage; Patent Term; Patentability Criteria; Plant Variety Protection (PVP); Situation Complaints; Traditional Knowledge; TRIPS; TRIPS Council; TRIPS Plus; TRIPS-Plus Provisions; Unilateral Coercive Measures; Vienna Convention on the Law of Treaties (VCLT); World Trade Organization (WTO); WTO